2021
DOI: 10.1177/1468798421995527
|View full text |Cite
|
Sign up to set email alerts
|

Designing on the page: Composing picturebooks in a Kevin Henkes author study

Abstract: A team of four general education second grade teachers, who work in a neighbourhood state elementary school in a large urban area in the northeast United States, and their staff developer, redesigned their Kevin Henkes Author Study to equally value pictures and design, along with writing. They asked, what narrative understandings do children express by designing on the page? Using a framework of multiliteracies, they showed how they transformed writing workshop into composing workshop to support their emergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Aligned with previous research findings that revealed the importance of affording students with opportunities to engage in transduction through talking and/or writing about their multimodal processes and products (Dallacqua, 2018; Kesler et al, 2021; Lim et al, 2022; Mills & Doyle, 2019; Pantaleo, 2015, 2019a, 2019b), the Grade 4 students' semiotic work underscores the multifaceted importance of student engagement in retrospective accounting and/or analysing of their multimodal representations. In the opinion of Kress (2010), “signs made ‘outwardly’ are the best evidence … for understanding the ‘inner’ processes of learning” (p. 183).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Aligned with previous research findings that revealed the importance of affording students with opportunities to engage in transduction through talking and/or writing about their multimodal processes and products (Dallacqua, 2018; Kesler et al, 2021; Lim et al, 2022; Mills & Doyle, 2019; Pantaleo, 2015, 2019a, 2019b), the Grade 4 students' semiotic work underscores the multifaceted importance of student engagement in retrospective accounting and/or analysing of their multimodal representations. In the opinion of Kress (2010), “signs made ‘outwardly’ are the best evidence … for understanding the ‘inner’ processes of learning” (p. 183).…”
Section: Discussionsupporting
confidence: 74%
“…As noted above, the students' transmodal meaning‐making required engagement in medium‐specific analysis (Suhor, 1984) and use of appropriate metalanguage to explicate how their deliberate use of elements of visual art and design and comics conventions fulfilled communicative purposes and addressed assignment criteria. These findings augment previous studies where researchers have reported on how the explicit instruction of appropriate metalanguage informed and enhanced both student interpretation and analysis of multimodal texts, such as picturebooks (e.g., Macken‐Horarik, 2016; Martens et al, 2012/2013; Pantaleo, 2016, 2018a, 2021; Unsworth & Macken‐Horarik, 2015) and graphic novels (e.g., Connors, 2013; Dallacqua, 2018; Pantaleo, 2014, 2018b), and student design and analysis of their own multimodal ensembles (Dallacqua, 2018; Kesler et al, 2021; Lim et al, 2022; Mills & Doyle, 2019; Pantaleo, 2015, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the use of learning media can foster new desires and interests, motivation, and stimulation in learning, and even have a psychological influence on students in learning (Endiawan et al, 2021). Through the Pictorial Media Story, there is a lot of interaction between students and teachers and students and students (Kesler et al, 2021). All students are required to be able to speak in class, so it is not only smart students who often speak.…”
Section: Post-test Resultsmentioning
confidence: 99%